2014
DOI: 10.7183/1045-6635.25.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the Glyphic Texts of Tipan Chen Uitz, Cayo District, Belize

Abstract: The 2011 investigations of the Caves Branch Archaeological Survey at the large and recently documented Maya site of Tipan Chen Uitz resulted in the discovery of the site's first monument with a glyphic inscription. Prior to this discovery, the site's glyphic corpus was limited to a small collection of texts rendered on fragmentary ceramics. In this paper, we describe these sherds as well as the monument (Monument 1), report on their archaeological contexts, provide an epigraphic analysis of the texts, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…In an ethnographic study of Kekchi Maya from southern Belize, Wilk (, p. 53) pointed out that intensification of agriculture causing pressures on land resources was not primarily related to population pressure, but instead typically results following the addition of cash crops to the subsistence system. While the rural Protoclassic communities in the Roaring Creek Valley did not experience significant population pressure and overcrowding, ceramic evidence of extensive trade ties with the urban centers in the nearby Belize River Valley suggests increasing interaction with market economies could have disrupted agricultural production (Andres et al, ). Thus, it may be that this heightened participation in trade led to an increased focus on cash crops, such as cacao, that may have resulted in reduced dietary variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ethnographic study of Kekchi Maya from southern Belize, Wilk (, p. 53) pointed out that intensification of agriculture causing pressures on land resources was not primarily related to population pressure, but instead typically results following the addition of cash crops to the subsistence system. While the rural Protoclassic communities in the Roaring Creek Valley did not experience significant population pressure and overcrowding, ceramic evidence of extensive trade ties with the urban centers in the nearby Belize River Valley suggests increasing interaction with market economies could have disrupted agricultural production (Andres et al, ). Thus, it may be that this heightened participation in trade led to an increased focus on cash crops, such as cacao, that may have resulted in reduced dietary variability.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary isotopic analysis shows that individuals buried at AUK were local (Wrobel et al, ). Recent archaeological research has demonstrated that this area was a rural hinterland with small farming communities at the time AUK was used for burial, with no evidence for complex social hierarchy or dense settlement prior to the sudden construction of monumental centers in the 7th century AD (Andres et al, ).…”
Section: A New Context For Scurvy In Central Belizementioning
confidence: 99%
“…Of particular relevance to our research is the civic-ceremonial centre of Tipan Chen Uitz, first documented in 2009 (Andres et al 2010, 2014). In addition to its large size and architectural complexity, Tipan is distinguished by its physical integration with surrounding minor centres via an extensive network of causeways (or sacbeob ) (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…Surface sites recorded to date range in size from isolated house mounds, to patio-focused residential clusters, to large conglomerations of monumental architecture that can be classed as first- and second-order central places (Helmke & Awe 2012; Andres et al . 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our survey and excavations at Tipan Chen Uitz (Figure 2) have yielded evidence that it was a regional capital with ties to powerful foreign polities, as attested by the discovery of multiple carved stone monuments (Figure 3; see Andres et al . 2014; Helmke & Andres 2015; Andres et al . in press in Antiquity ).…”
mentioning
confidence: 99%